Effect in comparison between intrathecal dexmedetomidine and intrathecal fentanyl added to bupivacaine in lower limb orthopaedic surgeries - Mariah, Subashini A/P (2015)

(untitled)
Introduction: Various adjuvants have been used with local anaesthetics in spinal anaesthesia to avoid intraoperative visceral and somatic pain and to provide prolonged postoperative analgesia. Dexmedetomidine, the new highly selective α2-agonist drug, is now being used as a neuraxial adjuvant. Objectives: The purpose of this study was to evaluate the onset and duration of sensory and motor block as well as postoperative analgesia and adverse effects of dexmedetomidine or fentanyl given intrathecally with hyperbaric 0.5% bupivacaine for spinal anaesthesia in lower limb orthopaedic surgeries. This study was conducted in Hospital Universiti Sains Malaysia, Kelantan. Methodology: Sixty four patients classified as American Society of Anesthesiologists (ASA) status I and II scheduled for lower limb orthopaedic surgeries were prospectively studied. Patients were randomly allocated to receive intrathecally either 2.5 mls hyperbaric 0.5% bupivacaine plus 5 μg dexmetedomidine (n=32) or 2.5 mls hyperbaric 0.5% bupivacaine plus 25 mg fentanyl (n = 32), the onset time to reach peak sensory and motor level, the regression time for sensory and motor block, haemodynamic changes, postoperative time to rescue analgesia with total dosage of voltaren in first 24 hours and side effects were recorded by an anaesthetist colleague blinded to the groups. Results: Patients in the dexmedetomidine group had a significantly longer sensory and motor block time than patients in fentanyl group. The mean time of sensory regression to S1 was 323.75±20.28 min in dexmedetomidine group and 256.56±33.76 min in fentanyl group (P<0.001). The mean regression time of motor block to reach modified Bromage 0 was 271.56±24.64 min in dexmedetomidine group and 202.81±44.09 min in fentanyl group (P<0.001). Postoperative analgesic requirements were less and time to rescue analgesia were prolonged in dexmedetomidine group compared to fentanyl. Mean time to rescue analgesia was 8.84±0.57 minute in dexmedetomidine group compared to 7.53±0.57 minutes in fentanyl group (p<0.001). There were no significant difference in the adverse effect of both the drugs. Conclusions: Intrathecal dexmedetomidine is associated with prolonged motor and sensory block, haemodynamic stability, and reduced demand for rescue analgesics in 24 h as compared to fentanyl.